Coup, riot, war: how political institutions and ethnic politics shape alternative forms of political violence - Choi, Hyun Jin (Terrorism and political violence, 2018)
This article explores how different types of governance systems shape different forms of political violence. We identify four governance types by combining the “institutional” dimension of coalition size represented by a minimum winning coalition (MWC) and the “ethno-political” dimension represented by the size of ethnic groups participating in the governing coalition. This study hypothesizes that (a) an exclusive system (small MWC; narrow-based ethnic coalition) is likely to engender civil war, (b) an oversized system (small MWC; broad-based ethnic coalition) is likely to generate a coup, and (c) an undersized system (large MWC; narrow-based ethnic coalition) is likely to stimulate riots or protests. Statistical analyses confirm all three hypotheses, implying that opposition groups choose alternative forms of conflict that maximize their chances of accessing power under different governance configurations. The article concludes by identifying three possible paths toward inclusive governance and suggesting that institutional reform before ethnic inclusion makes a transition toward inclusive governance far less dangerous.